Effects of Nicotine Metabolic Rate on Withdrawal Symptoms and Response to Cigarette Smoking After Abstinence. Issue 3 (25th October 2018) - Liakoni, Evangelia; Edwards, Kathryn C.; St. Helen, Gideon; Nardone, Natalie; Dempsey, Delia A.; Tyndale, Rachel F.; Benowitz, Neal L.
Abstract : This study investigated the influence of the rate of nicotine metabolism, as indicated by the nicotine metabolite ratio (NMR), on tobacco dependence. We stratified 136 smokers on the basis of saliva NMR as fast ( n  =   65) and slow ( n  =   71) metabolizers. Two "loading cigarettes" were smoked after overnight, and a "reward cigarette" was smoked after 6 hours of daytime, abstinence. Blood nicotine concentrations, expired carbon monoxide, withdrawal/craving, and reward questionnaires were collected before/after smoking and during daytime abstinence. Compared with slow metabolizers, fast metabolizers had a shorter nicotine elimination half‐life ( P  < 0.001), lower plasma nicotine concentrations ( P  < 0.001), and higher withdrawal/craving scores ( P  < 0.05) for most times during daytime abstinence, indicating that fast metabolizers are likely smoking more to relieve withdrawal symptoms (negative reinforcement). Reward/satisfaction scores were similar in fast and slow metabolizers, suggesting that faster nicotine metabolism, assessed by NMR, is not associated with greater positive reinforcement. CYP2A6 normal ( n  =   82) and reduced ( n  =   42) genotype predicted plasma nicotine concentrations but not withdrawal symptoms.